ANALYSIS IMPACT OF BSI MERGER - Husnaini; Sutan Emir Hidayat Taufiq (IRTIQO' : Postgraduate Journal of Islamic Economics, Finance and Accounting Studies, 2025)
This study aims to analyze the impact of the Bank Syariah Indonesia (BSI) merger on the performance of Islamic stocks in the Indonesian financial sector. The merger of three state-owned Islamic banks (BRI Syariah, BNI Syariah, and Bank Syariah Mandiri) is a strategic government policy to strengthen the national Islamic banking industry, increase economies of scale, and expand Indonesia's influence in the global Islamic financial market. The method used is a quantitative descriptive approach with a Vector Error Correction Model (VECM) approach involving stock price and transaction volume variables from four Islamic banks: Bank Syariah Indonesia (BRIS), Bank Aladin (BANK), Bank BTPN Syariah (BTPS), and Bank Panin Dubai Syariah (PNBS). The data used is weekly data for the 2018–2023 period. It results of the study indicate that the BSI merger had a negative and significant impact on the stock prices and transaction volume of BANK, BTPS, and PNBS. However, PNBS transaction volume showed a positive and significant response to its internal variables. The VECM results found a short-term influence between BRIS stock prices and BANK, BTPS, and PNBS. The Granger causality test showed a one-way relationship between BRIS stock prices and several other sharia stock variables. Meanwhile, the Impulse Response Function (IRF) results showed that BRIS shares responded positively when other variables experienced shocks. In general, sharia stocks in the financial sector exhibited adaptive fluctuations and followed model predictions. Key Words : Sharia Stock, merger Bank Syariah Indonesia, financial sector of Islamic Index